Design of Regenerative Braking System and Energy Storage with Supercapacitors as Energy Buffers - Michael, Siluvai M.; Mtengi, Bokani; Prabaharan, S. R. S; Zungeru, Adamu Murtala; Ambafi, James Garba (International Journal of Electrical and Computer Engineering Systems, 2024)
Vehicles are part of urban area transport and are subjected to variable loads as they traverse the city with varying slopes and stop-and-go traffic. Electric Vehicles (EVs) can be a good option because of their high efficiency under stop-and-go conditions and ability to gain energy from braking. However, limited battery energy makes EVs less efficient and degrades their lifetime. In contrast to a Li-Ion battery, supercapacitors work well under high power charge and discharge cycles. However, their high cost and low energy density prevent them from being viable replacements for batteries. Due to the slow charging and discharging process of batteries, they have a low power density, but a high energy density compared to the supercapacitor. In this paper, we discussed our system design consisting of both a battery and a supercapacitor. The main aim is to design and develop a scheduling algorithm to optimize energy flow between the battery, supercapacitor, and motor. We further described an analogue-based control methodology and algorithm for the supercapacitor, augmented battery-powered motoring process. This is in addition to a charge controller designed to optimize the supercapacitor bank’s current-based charge-discharge profile. The system design and tests are developed on PSPICE and a hardware platform.